The Co-Movements of Credit Default Swap Spreads in China. Issue 5 (9th April 2023) - Wang, Xiaoxuan; Wang, Xinjie; Zhao, Suyang
ABSTRACT: In this paper, we study systemic risk in China using information from the credit default swap (CDS) data of Chinese firms. We find a large time variation in CDS spreads. More importantly, firms' CDS spreads co-move with each other and the first three principal components (PCs) explain 94% of the time-series variation in CDS spreads. We further identify a set of economic risk factors that drive the co-movement of CDS spreads. Large external economic shocks shift a significant proportion of the variance explanation power from the factors related to China's domestic economic condition to foreign trade and money supply. Our results reveal the sources and dynamics of systemic risk in China.